Keanekaragaman polen sebagai sumber pakan lebah Trigona sp. di Desa Sukawening Kecamatan Dramaga Kabupaten Bogor - Triyadi, Ryan; Triastinurmiatiningsih, Triastinurmiatiningsih; Moerfiah, Moerfiah (Jurnal Biologi Udayana; Vol 27 No 1 (2023): JURNAL BIOLOGI UDAYANA, 2023)
Stingless bees generally produce honey products, but there is also pollen that can be studied in melissopalinology to identify pollen morphology, type and geography of plants. Pollen can also reveal the feeding aspects of stingless bees that are useful for their survival. This study was conducted to identify the diversity of pollen used as a food source for stingless bees Trigona sp. in Sukawening Village, Dramaga District, Bogor Regency. The research method used was the extraction of pollen from honey, acetolysis, identification and calculated the percentage of pollen. The results obtained 24 types of pollen (4 species have not been identified) which belong to 19 families and the dominant source of pollen comes from herbaceous plants. The percentage of pollen collected from Trigona sp. in Sukawening Village, Dramaga District, Bogor Regency is dominated by Cocos nucifera which is 11.03% categorized as Important Minor Pollen Type (IMPT) (3-15%).